Purification and quantitative proteomic analysis of cell bodies and protrusions - Dermit, Maria (STAR Protoc, 2021)
Actin-rich protrusions are membrane extensions generated by actin polymerization that drive mesenchymal-like cell migration. Characterization of protrusions proteome is crucial for understanding their function. We present a complete step-by-step protocol based on microporous filter-based fractionation of protrusive cellular domains coupled with sample preparation for quantitative proteomics, mass spectrometric data acquisition, and data analysis. This protocol enables purification, quantification, and analysis of the distribution of proteins present in protrusions and cell bodies. For complete details on the use and execution of this protocol, please refer to Dermit et al. (2020).